The Dividend Puzzle A Progress Report by Steven V. Mann (1989): A Review with Insights from Philippines’ New Corporate Tax Law - Conales, Madelle (Business and Economic Research, 2022)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">This research reviews the progress of the “dividend puzzle” in the finance literature. The article tracks the theoretical evolution of dividend policy and its conceptual and practical differences throughout the years. As such, this paper gives an updated literature discussion on the dividend policies of corporations, its impact to investor preferences, and the linkage to corporate taxes. This literature review implies that the “dividend puzzle” remains unsolved and continues to be an intriguing subject matter as academicians and practitioners alike cannot exactly explain the behavior of investors and corporations as seen in the decades of corporate dividend policies. Furthermore, this article ends with a brief update regarding Philippine’s new Corporate Tax Law (CREATE Law) and author’s brief perspective on dividend policies.